(untitled) (Academia Science Repository, 2023)
In the article, implementation of comprehensive measures in the field of state cadastres, management of the state cadastral system, determination of distribution limits of natural and socio-economic resources, quantitative and qualitative description of land by types, assessment of their economic, ecological and social conditions the issues of learning ways to give and use them rationally are covered. Also, information about the content of large-scale cadastral cards, their importance in the national economy, and the use of conventional signs is presented.